Analysis of Volatile Molecules Present in the Secretome of the Fungal Pathogen Candida glabrata - López-Ramos, Juan Ernesto (Molecules, 2021)
Candida albicans, Candida glabrata, Candida parapsilosis and Candida tropicalis are the four most common human fungal pathogens isolated that can cause superficial and invasive infections. It has been shown that specific metabolites present in the secretomes of these fungal pathogens are important for their virulence. C. glabrata is the second most common isolate world-wide and has an innate resistance to azoles, xenobiotics and oxidative stress that allows this fungal pathogen to evade the immune response and persist within the host. Here, we analyzed and compared the C. glabrata secretome with those of C. albicans, C. parapsilosis, C. tropicalis and the non-pathogenic yeast Saccharomyces cerevisiae. In C. glabrata, we identified a different number of metabolites depending on the growth media: 12 in synthetic complete media (SC), 27 in SC-glutamic acid and 23 in rich media (YPD). C. glabrata specific metabolites are 1-dodecene (0.09 ± 0.11%), 2,5-dimethylundecane (1.01 ± 0.19%), 3,7-dimethyldecane (0.14 ± 0.15%), and octadecane (0.4 ± 0.53%). The metabolites that are shared with C. albicans, C. glabrata, C. parapsilosis, C. tropicalis and S. cerevisiae are phenylethanol, which is synthesized from phenylalanine, and eicosane and nonanoic acid (identified as trimethylsilyl ester), which are synthesized from fatty acid metabolism. Phenylethanol is the most abundant metabolite in all fungi tested: 26.36 ± 17.42% (C. glabrata), 46.77 ± 15.58% (C. albicans), 49.76 ± 18.43% (C. tropicalis), 5.72 ± 0.66% (C. parapsilosis.) and 44.58 ± 27.91% (S. cerevisiae). The analysis of C. glabrata’s secretome will allow us to further our understanding of the possible role these metabolites could play in its virulence.